Measuring Heterogeneity in Job Finding Rates Among the Nonemployed Using Labor Force Status Histories - Marianna Kudlyak; Fabian Lange (Institute for the Study of Labor (IZA), 2014)
We use a novel approach to studying the heterogeneity in the job finding rates of the nonemployed by classifying the nonemployed by labor force status (LFS) histories, instead of using only one-month LFS. Job finding rates differ substantially across LFS histories: they are 25-30% among those currently out of the labor force (OLF) with recent employment, 10% among those currently OLF who have been unemployed but not employed in the previous two months, and 2% among those who have been OLF in all three previous months. This heterogeneity cannot be deduced from the one-month LFS or from one-month responses to the CPS survey questions about desire to work or recent search activity. We conclude that LFS histories is an important predictor of the nonemployed's job finding probability, particularly for those OLF.
Keywords: E24; E32; J21; J22; J30; J41; J60; J63; J64; 330; job finding rate; search process; out of the labor force (OLF); heterogeneity; unemployment